2017
DOI: 10.31276/vjste.59(2).34
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable rice cultivation in the deep flooded zones of the Vietnamese Mekong Delta

Abstract: Abstract:This paper explains how the management of the full-dyke system in the deep flooded zones of the Vietnamese Mekong Delta affects rice cultivation, and outlines how alternative dyke management strategies could offer more sustainable adaptations in the face of future environmental threats. The current management of the 'full-dyke' network has been successful in promoting triple-cropping rice cultivation, but this practice has prevented sediment deposition on the land surface. River-borne sediments deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Therefore, the agricultural sector has to spend more money on providing nutrients to the soil (People's Committee of An Giang Province, 2021). This result is also in line with a study indicating that changes in flood water level affect nutrients for the VMD and An Giang Province, and nutrients available from flood water potentially have a value of 26 million USD per year of free fertilizer to An Giang Province (Bui & Nguyen, 2021; Chapman et al, 2017).…”
Section: Resultssupporting
confidence: 90%
“…Therefore, the agricultural sector has to spend more money on providing nutrients to the soil (People's Committee of An Giang Province, 2021). This result is also in line with a study indicating that changes in flood water level affect nutrients for the VMD and An Giang Province, and nutrients available from flood water potentially have a value of 26 million USD per year of free fertilizer to An Giang Province (Bui & Nguyen, 2021; Chapman et al, 2017).…”
Section: Resultssupporting
confidence: 90%
“…A minority, yet growing amount, of studies no longer solely ascribe changes in the region to climate change, but to broader changes, including land-use challenges, government policy, geopolitical relations, and transboundary water governance issues (Tran, 2020b). The studies establish links between (out)migration and failure to adapt to agricultural intensification (Chapman et al, 2017), land-use change and lack of employment opportunities (Tran, 2019;Tran & James, 2017, and government policy (Danh & Mushtaq, 2011). On the other hand, we found that the majority of the studies (61%) still established a direct relationship between environmental or climate risk and human mobility.…”
Section: Academic Studiesmentioning
confidence: 99%
“…Delta subsidence, driven by compaction of sedimentary strata 13 , is also being accelerated due to increased rates of ground water extraction 14,15 . Furthermore, many large deltas are also sediment starved 16 due to major reductions in the supply of fluvial sediment caused by upstream dam construction 17,18 , rapid and accelerating sand mining 19,20 , and the construction of flood embankments 12,21,22 . Such sediment starvation potentially compromises the ability of deltas to offset rising sea-levels through sediment deposition 1,23 .…”
Section: Here We Use New Field Data and Hydrodynamic Modelling To Quamentioning
confidence: 99%